PELAKSANAAN TUGAS PENYIAPAN AGENDA PIMPINAN DI BAGIAN PROTOKOL SEKRETARIAT DAERAH KABUPATEN SIKKA - Maria Ritkalivan; Markus Kristian Retu; Intan Mustafa (CENDEKIA: Jurnal Ilmu Pengetahuan, 2026)
The implementation of leaders’ agenda management is a strategic function in supporting the effectiveness of local government administration. The Protocol Section of the Regional Secretariat of Sikka Regency plays an important role in managing leaders’ agendas through planning, coordination, protocol implementation, as well as documentation and publication of leaders’ activities. This study aims to describe and analyze the implementation of leaders’ agenda management in the Protocol Section of the Regional Secretariat of Sikka Regency and to identify the constraints encountered in its implementation. This research employs a qualitative approach with a descriptive method. Data were collected through in-depth interviews, observation, and documentation, with informants selected purposively from officials directly involved in managing leaders’ agendas. The results indicate that the implementation of leaders’ agenda management has generally been carried out in accordance with the duties and functions of the Protocol Section, particularly in scheduling, protocol implementation, and coordination of leaders’ activities. However, several constraints were identified, including sudden changes in agendas, limited human resources, suboptimal inter-agency coordination, and limited information technology support This study concludes that strengthening human resource capacity, improving coordination among regional agencies, and optimizing the use of information technology are necessary to enhance the effectiveness of leaders’ agenda management within the Government of Sikka Regency. ABSTRAK Pelaksanaan tugas agenda pimpinan merupakan salah satu fungsi strategis dalam mendukung kelancaran penyelenggaraan pemerintahan daerah. Bagian Protokol Sekretariat Daerah Kabupaten Sikka memiliki peran penting dalam mengelola agenda pimpinan melalui perencanaan, koordinasi, pelaksanaan keprotokolan, serta dokumentasi dan publikasi kegiatan pimpinan daerah. Penelitian ini bertujuan untuk mendeskripsikan dan menganalisis pelaksanaan tugas agenda pimpinan di Bagian Protokol Sekretariat Daerah Kabupaten Sikka serta mengidentifikasi kendala yang dihadapi dalam pelaksanaannya. Penelitian ini menggunakan pendekatan kualitatif dengan metode deskriptif. Teknik pengumpulan data dilakukan melalui wawancara mendalam, observasi, dan dokumentasi, dengan informan yang dipilih secara purposive dari aparatur yang terlibat langsung dalam pengelolaan agenda pimpinan. Hasil penelitian menunjukkan bahwa pelaksanaan tugas agenda pimpinan pada dasarnya telah berjalan sesuai dengan tugas dan fungsi Bagian Protokol, khususnya dalam penyusunan jadwal, pelaksanaan keprotokolan, serta koordinasi kegiatan pimpinan. Namun demikian, masih ditemukan beberapa kendala, seperti perubahan agenda secara mendadak, keterbatasan sumber daya manusia, koordinasi lintas perangkat daerah yang belum optimal, serta keterbatasan sarana pendukung berbasis teknologi informasi. Penelitian ini menyimpulkan bahwa peningkatan kapasitas aparatur, penguatan koordinasi, dan optimalisasi pemanfaatan teknologi informasi diperlukan untuk meningkatkan efektivitas pelaksanaan tugas agenda pimpinan di lingkungan Pemerintah Kabupaten Sikka.